2014
DOI: 10.1136/acupmed-2014-010580
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Acupuncture: Why Are We Not Using It?

Abstract: Acupuncture is mostly known to the general readership for its analgesic effects. 1 Focusing on the treatment of acute postoperative pain, a meta-analysis of 15 randomised controlled trials (RCTs) comparing acupuncture with sham control in the management of postoperative pain showed that acupuncture decreased both pain intensity and opioid consumption up to 72 h after surgery. 2 This opioid reduction effect was associated with a decreased incidence of opioid-related side effects such as nausea, dizziness, sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our systematic review found that trials in which acupuncture was administered postoperatively showed inconsistent results in the prevention of PONV in patients with colorectal cancer 5. Although it is plausible that sensory stimulation triggering favourable physiological responses to prevent PONV would not be obtained under general anaesthesia,9 10 favourable effects of the perioperative administration of acupuncture, including intraoperative stimulation, were observed in some trials 1112 While specific recommendations cannot be made due to a paucity of evidence, the perioperative administration (ie, preoperative, intraoperative and postoperative) of acupuncture stimulation was chosen for the maximum possible benefit in our trial.…”
Section: Methods and Analysismentioning
confidence: 97%
“…Our systematic review found that trials in which acupuncture was administered postoperatively showed inconsistent results in the prevention of PONV in patients with colorectal cancer 5. Although it is plausible that sensory stimulation triggering favourable physiological responses to prevent PONV would not be obtained under general anaesthesia,9 10 favourable effects of the perioperative administration of acupuncture, including intraoperative stimulation, were observed in some trials 1112 While specific recommendations cannot be made due to a paucity of evidence, the perioperative administration (ie, preoperative, intraoperative and postoperative) of acupuncture stimulation was chosen for the maximum possible benefit in our trial.…”
Section: Methods and Analysismentioning
confidence: 97%
“…So the question whether acupuncture can reduce the dosage of sedative, and be implemented into the clinical routine as a complementary sedative method has still to be answered [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the evidence, acupuncture in the peri-operative setting has largely remained at the research stage. Although used by individual, interested anaesthetists, 6 to date it has not been implemented systematically. Clinicians involved in peri-operative care from Norway, Germany and the United States have questioned why this safe, simple and effective therapy has not been routinely implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians involved in peri-operative care from Norway, Germany and the United States have questioned why this safe, simple and effective therapy has not been routinely implemented. 5,6 According to the Diffusion of Innovation Theory, 7 positive attitudes towards an innovation, perceived need for change and openness to new ideas are features of early adopters of innovations and facilitate uptake and implementation. 8 A recent survey studied the knowledge and attitudes of 292 anaesthesia providers from the United States towards the use of A/A for PONV 9 and found an overall positive attitude and receptivity to A/A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation